2015
DOI: 10.1088/0004-637x/806/1/24
|View full text |Cite
|
Sign up to set email alerts
|

EXTRAGALACTIC STAR-FORMING GALAXIES WITH HYPERNOVAE AND SUPERNOVAE AS HIGH-ENERGY NEUTRINO AND GAMMA-RAY SOURCES: THE CASE OF THE 10 TeV NEUTRINO DATA

Abstract: In light of the latest IceCube data, we discuss the implications of the cosmic ray (CR) energy input from hypernovae and supernovae into the Universe, and their propagation in the hosting galaxies and galaxy clusters or groups. The magnetic confinement of CRs in these environments may lead to efficient neutrino production via pp collisions, resulting in a diffuse neutrino spectrum extending from PeV down to 10 TeV energies, with a spectrum and flux level compatible with that recently reported by IceCube. If th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 79 publications
4
77
0
Order By: Relevance
“…4 indicates the the optimistic upper limit can exceed the IceCube data in principle. The spectral shape is suggestive as it is globally soft for 10 TeV E ν 5 PeV, but avoids the constraints set by the Fermi extragalactic gamma-ray background measurement in the sub-TeV range [93][94][95].…”
Section: Diffuse Neutrinos From Low-luminosity Grbs and Hypernovaementioning
confidence: 99%
“…4 indicates the the optimistic upper limit can exceed the IceCube data in principle. The spectral shape is suggestive as it is globally soft for 10 TeV E ν 5 PeV, but avoids the constraints set by the Fermi extragalactic gamma-ray background measurement in the sub-TeV range [93][94][95].…”
Section: Diffuse Neutrinos From Low-luminosity Grbs and Hypernovaementioning
confidence: 99%
“…Clusters and groups of galaxies have also been investigated as potential neutrino sources [40,47], where cosmic rays, generated through large-scale-structure shocks [37,40] or injected by star-forming galaxies [27], interact with the intracluster medium. Since the cluster or group number density decreases as a function of redshift, implying a small value of δ, tomographic constraints are very stringent.…”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 99%
“…Many papers discuss the neutrino emission from one specific source class by adopting a modeldependent approach, for active galactic nuclei (AGNs) [9][10][11][12][13][14][15][16][17][18], star-forming galaxies [19][20][21][22][23][24][25][26][27][28], gamma-ray bursts [29][30][31][32][33][34][35][36], galaxy clusters [37][38][39][40], and dark matter decays [41][42][43][44][45].…”
mentioning
confidence: 99%
“…Various extragalactic scenarios have been suggested that might be (partially) responsible for the observed flux of neutrinos. Source candidates include galaxies with intense star formation [28,29,30,31,32,33], cores of active galactic nuclei (AGN) [34,35,36], low-luminosity AGN [37,38], blazars [39,40,41], low-power GRBs [42,43,44], cannonball GRBs [45], intergalactic shocks [46], and active galaxies embedded in structured regions [47,48,29].…”
Section: Pos(icrc2015)022mentioning
confidence: 99%